Queuing Problems in Pharmacies - Rhemtula, Zuleika Goolam (My University, 2011)
This research report investigated demand and supply factors affecting pharmaceutical services and assisted with making recommendations to the Steve Biko Academic Hospital management on how to reduce the mean waiting times and to improve the actual and perceived customer services at the SBAH outpatient pharmacy. The demand and supply of pharmaceutical services was investigated through a quantitative methodology, using data collection forms to quantify the factors affecting queues at the Steve Biko Academic Hospital outpatient pharmacy. The qualitative methodology observed the layout, processes and the attitude of staff, using an unstructured observation checklist; with the intention of providing clarity and explanation for the quantitative findings of this research. The findings of this research will serve as historical standards or baseline measures against which future performance can be measured. The recommendations to improve the waiting time at the Steve Biko Academic Hospital‟s out patient pharmacy were categorised into infrastructure, demand management and supply management recommendations. The infrastructure and supply management recommendations will improve efficiencies within the outpatient pharmacy however, the implementation of the demand management strategies will provide a greater impact on the waiting times of the patients at the Steve Biko academic hospital‟s out patient pharmacy
MBA - WBS
Keywords: Pharmacies; Health care sector; Hospitals; Queuing models